Psychological variables in ascertaining potential archers - Rabiu Muazu, Musa; Zahari, Taha; Anwar, P. P. Abdul Majeed; Mohamad Razali, Abdullah (Springer Singapore, 2019)
This chapter evaluates the relationship of athletic psychological coping skills with the archers’ performance. It was demonstrated from the study that the possession of certain psychological coping skills, namely coping with adversity, coachability, peaking under pressure, concentration, confidence and achievement motivation, goal setting and mental preparation is non-trivial in the achievement of high archery shooting score. It was also shown that the tansig-based ANN model could provide the better classification of HPA and LPA.